Analisis Agenda Setting Terhadap Kebijakan Pembentukan Daerah Otonomi Baru (Dob) (Studi Kasus Perencanaan Pemekaran di Kabupaten Bungo) - Rahmi, Helva (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2018)
This is the result of research on the stages of policy formation New Autonomous Region in Bungo. The regional growth is a product of public policy, as the government attempts to solve public problems in order to achieve an effective and efficient service. This study used a qualitative approach by combining the techniques of observation, interviews and document research. The purpose of this study to look at the stages of policy formation of the New Autonomous Region and the factors that hinder the stages of policy formulation formation of New Autonomous Region in Bungo. The results of this study indicate that the stages of policy formation Autonomous Region New Bungo is a stage that is quite complicated and it takes quite a long time which of a collective agreement becomes a public policy, many of the requirements that must be adapted to the conditions and capacity Bungo it itself, as well as various public polemics encountered during the stages of the formation of new autonomous regions.